Restoring cortical disinhibition improves Huntington’s disease phenotypes - Sonja Blumenstock; David Arakelyan; Nicholas del Grosso; Sonja Schneider; Yufeng Shao; Enida Gjoni; Rüdiger Klein; Irina Dudanova; Takaki Komiyama (Nature, 2026)
Abstract Huntington’s disease (HD) is a devastating movement disorder without a cure at present 1 . Although the monogenic basis of HD is well defined 2 , the complex downstream effects that underlie behavioural symptoms are poorly understood. These effects include cortical dysfunction 3,4 , yet the roles of specific cortical neuronal subtypes in HD symptoms remain largely unexplored. Here we used longitudinal in vivo two-photon calcium imaging to examine the activity of three cortical inhibitory neuron (IN) subtypes and excitatory corticostriatal (CStr) projection neurons in the motor cortex of the transgenic R6/2 HD mouse model throughout disease progression. We found that motor deficits in R6/2 mice were accompanied by neuron subtype-specific abnormalities in movement-related activity. This included marked hypoactivity of vasoactive intestinal peptide (VIP)-INs and CStr neurons, which was also observed in the knock-in zQ175DN HD mouse model. Optogenetic activation of VIP-INs in R6/2 mice restored healthy levels of activity in VIP-INs and their downstream CStr neurons and ameliorated motor deficits in R6/2 mice; behavioural improvements persisted for days after stimulation. Our findings highlight cortical INs as a potential therapeutic target for HD.